2000
DOI: 10.1017/s0954102000000031
|View full text |Cite
|
Sign up to set email alerts
|

Cephalopod diet of the southern elephant seal, Mirounga leonina, at King George Island, South Shetland Islands

Abstract: In the summer of 1995/96,25 southern elephant seals, Mirounga leonina, were stomach lavaged at Stranger Point, King George Island, South Shetland Islands. Cephalopod remains were present in 72% of the individuals sampled (n = 18). Seven species of squid and three of octopus were identified. The squid Psychroteuthis glacialis was the most important prey in terms of numbers (77%), biomass (80.8%) and frequency of occurrence (94.4%). Next in importance in terms of mass was the squid Alluroteuthis antarcticus (7.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 11 publications
0
51
0
1
Order By: Relevance
“…lanternfish) (Cherel et al 2008). Indeed, mycto phid (the abundant Electrona antarctica, E. carls bergi and Gymnoscopelus nicholsi) otoliths have been found in stomachs of SES from the Kerguelen sector (Slip 1995) and elsewhere (Daneri & Carlini 2002).…”
Section: Introductionmentioning
confidence: 99%
“…lanternfish) (Cherel et al 2008). Indeed, mycto phid (the abundant Electrona antarctica, E. carls bergi and Gymnoscopelus nicholsi) otoliths have been found in stomachs of SES from the Kerguelen sector (Slip 1995) and elsewhere (Daneri & Carlini 2002).…”
Section: Introductionmentioning
confidence: 99%
“…25 de Mayo population of M. leonina, studies have reported that juveniles (in their first year of life), females and adult males develop their foraging activity in different areas of the Southern Ocean (Bornemann et al, 2000;toSh et al, 2009). Additionally, dietary studies conducted to date on this population, have shown that its diet differs from those of other colonies since it is mainly represented by fish and squid species distributed almost entirely south of the Antarctic Polar Front (daneri et al, 2000daneri & carlini, 2002;PiatkowSki et al, 2002). Nevertheless, it should be noted that dietary information of the juvenile component of M. leonina in the Atlantic Sector of the Southern Ocean is relatively scarce.…”
mentioning
confidence: 97%
“…Cephalopods (squid and octopus) constitute a common prey in the diet of the southern elephant seal (clarke et al, 1982;rodhouSe et al, 1992;daneri et al, 2000), although fish have also been reported as a relatively important food item, at least seasonally (daneri & carlini, 2002;newland et al, 2009). The southern elephant seal has a key role as a top predator in the food webs of the southern marine ecosystem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Clarke (2007) suggested that sperm whales (Physeter macrocephalus) use seamounts as convenient 'restaurants' as they cross the abyssal plains. Elephant seals often include a large proportion of cephalopods in their diets (e.g., Clarke and MacLeod, 1982;Daneri et al, 2004;Green and Burton, 1993;Rodhouse et al, 1992;van den Hoff, 2004) and two male elephant seals from Marion Island made heavy use of the Funk and unnamed seamount in 2008 (Bester et al, 2009a, b), emphasizing the likely aggregation of cephalopods or fishes at these sites.…”
mentioning
confidence: 99%